Morphologic Change of In Vivo Porcine Liver Under 13 mm Hg Pneumoperitoneum Pressure. Issue 6 (December 2021) - Zhang, Wenyu; Yin, Dalong; Chen, Xiaoxia; Zhang, Shugeng; Meng, Fanzheng; Guo, Hongrui; Liang, Shuhang; Zhou, Shuo; Liu, Shuxun; Sun, Linmao; Guo, Xiao; Luo, Huoling; et al.
Abstract : Background: Clinically, the total and residual liver volume must be accurately calculated before major hepatectomy. However, liver volume might be influenced by pneumoperitoneum during surgery. Changes in liver volume change also affect the accuracy of simulation and augmented reality navigation systems, which are commonly first validated in animal models. In this study, the morphologic changes in porcine livers in vivo under 13 mm Hg pneumoperitoneum pressure were investigated. Materials and Methods: Twenty male pigs were scanned with contrast-enhanced computed tomography without pneumoperitoneum and with 13 mm Hg pneumoperitoneum pressure. Results: The surface area and volume of the liver and the vascular diameter of the aortic lumen, inferior vena cava lumen, and portal vein lumen were measured. There were statistically significant differences in the surface area and volume of the liver ( P =0.000), transverse diameter of the portal vein ( P =0.038), longitudinal diameter of the inferior vena cava ( P =0.033), longitudinal diameter of the portal vein ( P =0.036), vascular cross-sectional area of the inferior vena cava ( P =0.028), and portal vein ( P =0.038) before and after 13 mm Hg pneumoperitoneum pressure. Conclusions: This study indicated that the creation of pneumoperitoneum at 13 mm Hg pressure in a porcine causes liver morphologic alterations affecting the area and volume, as well as the diameter of a blood vessel.